Konflik Israel - Palestin dari aspek sejarah moden dan langkah pembebasan dari cengkaman Zionis (conflict Israel-Palestine from modern historical aspect and the step to liberate from Zionist clutched) - Nor, Mohd Roslan Mohd (Dept of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, Malaysia, 2010)
President of the United States, Obama, speaking in Cairo in June 2009, expressed deep sympathy to the Palestinians who have been oppressed for over a century. Zionist occupation of Palestine has changed the landscape of government in the Middle East. Some of the scholars believe that as long as the injustice committed by the Zionists, so long that there can be no peace in the region in particular and the world in general. This article is to review aspects of the modern history of the conflict and suggests some steps that can be brought to the goodness and global peace.